Revealing the blind spots: Five key challenges for advancing physician wellness - Neufeld, Adam (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Physician wellness is a critical yet unresolved challenge in medical education. Burnout, emotional distress, and systemic barriers undermine the sustainability of the healthcare workforce, with negative consequences for both physicians and patients. Despite widespread recognition, existing interventions often fall short, hindered by fragmented approaches and resistance to change. This article identifies five key challenges that will need to be overcome if we are to make meaningful progress in advancing physician wellness: (1) inconsistent definitions and flawed methodologies in assessing wellness, (2) overemphasis on individual-focused interventions, (3) the absence of unified, evidence-based frameworks, (4) ethical and methodological problems with wellness surveys, and (5) the commercialization of wellness. Each challenge represents deeply ingrained barriers within healthcare institutions that impede meaningful progress. I advocate for a paradigm shift toward evidence-based, systems-level strategies, focusing on Canadian and US medical education. By integrating theoretical frameworks like Self-Determination Theory (SDT) and the Job Demands-Resources (JDR) model into accreditation standards and institutional practices, healthcare organizations can address the root causes of physician distress.